FRENCH AS A FIRST FOREIGN LANGUAGE IN THE FINAL YEARS OF HIGH SCHOOL: TEXTBOOKS PUBLISHED IN SERBIA FROM 1957 TO THE PRESENT TODAY (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
Learning / teaching French in the last two years of high school is the subject of this article, made with the intention to, based on a summary, encourage thinking about possible further methodological and didactic activities and writing textbooks. By applying the descriptive and analytical-comparative method, ie exploratory-interpretative procedure, on the corpus of selected textbooks published in Serbia in the last sixty years, we came to the conclusion that in each methodological period there are textbooks whose concept is harmonized with knowledge relevant to learning French. language. We see the biggest difference in relation to foreign editions in the non-existence of multi-part textbook sets, ie in the existence of only one new textbook by Serbian authors in the 21st century.
Keywords: French language, textbooks, high school, goals, texts, activities, culture, orders